Anomalous Right Coronary Artery Originating From the Pulmonary Artery (ARCAPA): A Rare Presentation in the Fifth Decade. Issue 2 (March 2023) - Sharma, V.; Doig, F.; Maxwell, Ryan; Grout, D.; Saeed, U.; Wall, D.
Presented is a case report of a 54-year-old male Jehovah's Witness diagnosed with an anomalous right coronary artery originating from the main pulmonary artery with the initial presentation with a history of episodic fatigue, chest pain, palpitation, and bodily weakness. The patient was managed with reimplantation of the anomalous coronary artery onto the ascending aorta.